2019
DOI: 10.1136/bmjopen-2018-025524
|View full text |Cite
|
Sign up to set email alerts
|

Association of liver enzymes levels with fasting plasma glucose levels in Southern China: a cross-sectional study

Abstract: ObjectiveAccording to several studies, liver enzymes levels are associated with fasting plasma glucose (FPG) levels. However, the association stratified by body mass index (BMI) remains to be elucidated, especially in Southern China. Therefore, the aim of this study was to investigate the correlation between liver enzymes levels and FPG levels stratified by BMI in Southern China.DesignCross-sectional study.Participants and setting3056 individuals participated in real-time interviews and blood tests in Southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The plasma levels of liver enzymes have been shown to be positively correlated with FPG, and patients with T2D often have liver dysfunction. [54][55][56] Our results showed that the levels of ALT and AST were highest in the PD-B group rather than in the T2D group; therefore, liver function might have deteriorated before the FPG level reached the diagnostic threshold for T2D. Similarly, the level of UA increased as the FPG level increased but was highest in the PD-B group and decreased in the T2D group.…”
Section: Discussionmentioning
confidence: 90%
“…The plasma levels of liver enzymes have been shown to be positively correlated with FPG, and patients with T2D often have liver dysfunction. [54][55][56] Our results showed that the levels of ALT and AST were highest in the PD-B group rather than in the T2D group; therefore, liver function might have deteriorated before the FPG level reached the diagnostic threshold for T2D. Similarly, the level of UA increased as the FPG level increased but was highest in the PD-B group and decreased in the T2D group.…”
Section: Discussionmentioning
confidence: 90%
“…These enzymes utilize amino acids, such as L-alanine (ALT) and L-aspartate (AST), with 2-oxoglutarate derived from the tricarboxylic acid cycle to produce L-glutamate [100]. Increased plasma levels of these enzymes, regularly detected in type 2 diabetes, have been found to be associated with hyperinsulinemia, decreased insulin sensitivity, and hyperglycemia [101,102]. Moreover, the AST/ALT ratio was found to be negatively associated with type 2 diabetes [103106].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance, which is crucial in GDM development, may impair liver function and elevate ALT levels (Sakurai et al, 2021). GDM has been associated with metabolic disorders and chronic inflammation (Bakhshimoghaddam et al, 2023), potentially exacerbating liver stress and ALT levels (Huang et al, 2019). Moreover, the interplay between inflammation and insulin resistance could intensify GDM progression (Zheng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%